The Choking Game on YouTube: An Update. (16th March 2016) - Defenderfer, Ellen K.; Austin, Jillian E.; Davies, W. Hobart
The choking game (TCG) is an adolescent activity in which asphyxiation is used to obtain a "high, " occasionally resulting in seizures or death. A plethora of TCG information is available through YouTube, though this content has not been evaluated recently. The current study described TCG as portrayed in YouTube videos and compared views and ratings of TCG videos to unrelated videos. The TCG videos demonstrated diverse methods of asphyxiation, with a minority showing injury to the participants. TCG videos were less likely to be commented on or rated positively than non–choking game videos. TCG prevention videos differed significantly from actual TCG videos in the way they depicted the social context of TCG. Thus, TCG videos are accessible through YouTube, but the prevention materials available on YouTube are not accurate or representative. Accurate and educational online prevention materials should be created to decrease the occurrence of TCG.